Adhesion Properties Of Bifidobacterium Pseudocatenulatum G4 To Ht-29 Epithelium Cell Line - Suliman, Ali Kahtan (2009)

(untitled)
Bifidobacterium pseudocatenulatum G4 has been recently identified as a safe probiotic for incorporation into functional food for human consumption. Preliminary investigations showed that the probiotic candidate B. pseudocatenulatum G4 strain possesses the required criteria for a being successful probiotic microorganism. Further enhancement of these criteria was undertaken by studying the adherence and inhibition properties potential of this probiotic candidate. Human colon carcinoma epithelium cell line HT-29 was used to evaluate the adherence of B. pseudocatenulatum G4, in simulated environmental factors of the colon, namely pH, calcium ions, and cholic acid. The effect of this strain on enhancing intestinal tract resistance to pathogenic Escherichia coli and Clostridium infections was examined. Three different assays were used in order to differentiate between the competition, exclusion, and displacement of the pathogens by B. pseudocatenulatum G4. The adherence ability of B. pseudocatenulatum G4 to HT-29 cell line was investigated as in vitro model. In addition the morphology observation of the organism was done by using scanning electron microscopy (SEM). The effect of human colon environmental factors on the adhesion quality was studied. The results showed that the highest adhesion was in the ascending and transverse acidic regions of the colon. Calcium was shown to increase, while cholic acid was shown to decrease the adhesion of B. pseudocatenulatum G4 to HT-29. The inhibitory effect of B. pseudocatenulatum G4 on the adherence of Escherichia coli O157:H7, Clostridium scindens and Clostridium hiranonis was demonstrated. A decrease in the number of adhering pathogens was observed.